ANALISIS LOCATION QUOTIENT (LQ) TANAMAN TEBU (Saccharum officinarum L) di PROVINSI JAWA TENGAH - Widyastuti, Winda; Imanuddin, Muhamad (LPPM Universitas Malikussaleh - Indonesia, 2023)
Central Java Province is the center of sugar cane development which aims to increase sugar production. This research was conducted with the aim of identifying the sugarcane plantation base in regencies in Central Java Province. The method used in the analysis is Location Quotient (LQ) Analysis using secondary data regarding the planted area and production of sugar cane over the last five years, starting from 2018 to 2022. The results of the LQ analysis show that there are five districts with the largest planted area base for sugarcane large chilies, namely Kudus, Blora, Pati, Sragen, and Rembang Regencies. In addition, there are also five districts with the largest sugarcane production base, which include Kudus, Blora, Pati, Sragen and Rembang Regencies.